2020
DOI: 10.2139/ssrn.3556633
|View full text |Cite
|
Sign up to set email alerts
|

Coping Style, Social Support and Psychological Distress in the General Chinese Population in the Early Stages of the COVID-2019 Epidemic

Abstract: Background The purpose of this study was to investigate the psychological status of the general population in mainland China during the outbreak of coronavirus disease 2019 (COVID-19), and to explore the factors influencing psychological distress, in order to provide the basis for further psychological intervention programs. Methods We administered three questionnaires on-line to a convenience sample of the general population from different regions of mainland China from February 1 to February 4, 2020. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Further, positive coping strategies and increased social support were associated with decreased psychological distress, increased self-efficacy, improved sleep quality and decreased levels of anxiety and stress among nurses (Xiao, Zhang, Kong, Li, & Yang, 2020;Yu et al, 2020).…”
Section: Ta B L Ementioning
confidence: 99%
“…Further, positive coping strategies and increased social support were associated with decreased psychological distress, increased self-efficacy, improved sleep quality and decreased levels of anxiety and stress among nurses (Xiao, Zhang, Kong, Li, & Yang, 2020;Yu et al, 2020).…”
Section: Ta B L Ementioning
confidence: 99%
“…Therefore, measures to address loneliness among young people should be explored to prevent the occurrence of the associated mental health consequences. Social support, personal resilience, and coping abilities were identi ed as protective factors against adversity and stressful conditions such as disaster situations and disease outbreaks (Turner, 2015;Labrague et al, 2016;Yu et al, 2020;Xiao et al, 2020).). Available studies have shown that during stressful events, a resilient individual and those who have an adequate support system and coping skills are less likely to be stressed or feel lonely (Ogińska-Bulik & Michalska 2020;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Social support, personal resilience, and coping abilities were identi ed as protective factors against adversity and stressful conditions such as disaster situations and disease outbreaks (Turner, 2015;Labrague et al, 2016;Yu et al, 2020;Xiao et al, 2020).). Available studies have shown that during stressful events, a resilient individual and those who have an adequate support system and coping skills are less likely to be stressed or feel lonely (Ogińska-Bulik & Michalska 2020;Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%